Modeling and Implementation of a Web Database for RNA-Seq of Bovine Embryonic Cells - Daleffi, Natalia Soriani; Milazzotto, Marcella Pecora; Almeida, Fernanda Nascimento (Anais do Brazilian e-Science Workshop (BreSci), 2023)
This paper aims to develop a dedicated RNA-Seq database for bovine embryos, generated to gain insights into reproductive metabolism. The data is categorized into three groups, each obtained from distinct experiments. The primary objective is to streamline data analysis through a platform, named TranscriptomicsSeqDB, which standardizes and organizes RNA-Seq information from the Laboratory of Embryonic Metabolism and Epigenetics at UFABC, São Paulo, Brazil. Apart from data storage and management, TranscriptomicsSeqDB provides a user-friendly search interface with predefined queries to facilitate gene-specific indicator analysis.